2006
DOI: 10.1007/s00421-006-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

V max estimate from three-parameter critical velocity models: validity and impact on 800 m running performance prediction

Abstract: The purpose of this study was to evaluate the validity of maximal velocity (Vmax) estimated from three-parameter systems models, and to compare the predictive value of two- and three-parameter models for the 800 m. Seventeen trained male subjects (VO2max=66.54+/-7.29 ml min(-1) kg(-1)) performed five randomly ordered constant velocity tests (CVT), a maximal velocity test (mean velocity over the last 10 m portion of a 40 m sprint) and a 800 m time trial (V 800 m). Five systems models (two three-parameter and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
1
20
2
1
Order By: Relevance
“…Recently, Bosquet et al (2006) have shown that critical velocity determined by twoparameter hyperbolic model overestimated the real performance for the exercise duration of *136 s. In the same way, in the present study the CP model overestimated both the estimated I HIGH (EI HIGH ) and predicted I HIGH only for EC, presumably because the effect of reduced exercise duration on the estimates from CP model (Table 2; Fig. 6).…”
Section: Effects Of Training Statuscontrasting
confidence: 63%
See 2 more Smart Citations
“…Recently, Bosquet et al (2006) have shown that critical velocity determined by twoparameter hyperbolic model overestimated the real performance for the exercise duration of *136 s. In the same way, in the present study the CP model overestimated both the estimated I HIGH (EI HIGH ) and predicted I HIGH only for EC, presumably because the effect of reduced exercise duration on the estimates from CP model (Table 2; Fig. 6).…”
Section: Effects Of Training Statuscontrasting
confidence: 63%
“…Possible limitations of the CP model Some authors have indicated the limitation of the twoparameter CP model for estimating the intensity or T lim at high-intensity exercises (Hopkins et al 1989;Morton 1996;Bosquet et al 2006). Recently, Bosquet et al (2006) have shown that critical velocity determined by twoparameter hyperbolic model overestimated the real performance for the exercise duration of *136 s. In the same way, in the present study the CP model overestimated both the estimated I HIGH (EI HIGH ) and predicted I HIGH only for EC, presumably because the effect of reduced exercise duration on the estimates from CP model (Table 2; Fig.…”
Section: Effects Of Training Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Billat et al (2000) found that V max3par was not different from the maximum speed obtained in 20 m at maximal effort. However, Bosquet et al (2006) suggest that V max3par is smaller than the real V max (obtained by the average speed of the last 10 m of a maximal 40 m effort). Zacca et al (2010) found that V max was higher in sprint than endurance swimmers (2.53 ± 0.15 m·s -1 and 2.07 ± 0.19 m·s -1 respectively) independent of the mathematical model used (three or four parameters).…”
Section: Maximum Instantaneous Velocitymentioning
confidence: 83%
“…Com o objetivo de aprimorar o modelo de PC, foram elaborados mais dois modelos matemáticos (BOSQUET et al, 2006;2008, MORTON 1996 VERGAUWEN et al 1998;SMEKAL et al, 2000), badminton WONISCH et al 2003) e squash .…”
Section: Introductionunclassified